(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The paper focuses on the work of steel industrial fences in the conditions of the Far North, based on the results of the actual impact of snow masses. A computational model is developed for estimating the resulting stresses in the structure. Methods for assessing the impact of snow masses are proposed. The technologies of strengthening the existing fences are analyzed.